Autogenic Relaxation Therapy's Impact on Patients' Acute Pain Levels in Gladiol Ward RSUD Sukoharjo - Alfina Rahmadani; Arina Maliya (Jurnal EduHealth, 2025)
Acute pain in abdominal pain patients is a common problem that can affect quality of life. At RSUD Sukoharjo's Gladiol Ward, acute pain among patients experiencing abdominal pain is a prevalent issue, representing the highest percentage of complaints. Autogenic relaxation therapy has been proven effective in reducing various types of pain, but its effect on sharp pain in patients suffering from abdominal issues still needs further investigation. The current study will look at how autogenic relaxation therapy affects acute pain intensity in patients suffering from abdominal discomfort. A quasi pre-post test design was implemented in this research. Within this framework, the researcher assigned one group as the intervention group and the other as the control group. The study participants consisted of five inpatients at the Gladiol Ward, RSUD Sukoharjo, who were diagnosed with abdominal pain. Autogenic relaxation therapy was administered twice daily for three consecutive days, with pain levels assessed before and after the intervention using a numerical pain scale. Data analysis was conducted using the Paired T-Test, as the data followed a normal distribution. The statistical results indicated a significant reduction in acute pain levels after autogenic relaxation therapy at RSUD Sukoharjo. The Paired T-Test produced an Asymp. Sig.( 2-tailed ) value of 0.000. Since this value is less than 0,05. It confirms that the alternative hypothesis ( Ha ) is accepted. Therefore, autogenic relaxation therapy is proven to be effective in lowering acute pain levels in patients with abdominal pain. This study provides empirical evidence supporting the benefits of autogenic relaxation therapy as a non-pharmacologi approach to managing acute pain in patients with abdominal pain.